Diagnostic influence of cardiovascular screening by pocket-size ultrasound in a cardiac unit - Skjetne, Kyrre; Graven, Torbjørn; Haugen, Bjørn Olav; Salvesen, Øyvind; Kleinau, Jens Olaf; Dalen, Håvard (European journal of echocardiography, 2011)
We aimed to study the diagnostic influence of adding a routine cardiovascular ultrasound screening of the cardiac anatomy and function, the pericardium, the pleura and the abdominal great vessels by the new pocket-size ultrasound device (pUS) with grey scale and colour Doppler imaging. In 119 randomly selected patients admitted to a cardiac unit at a non-university hospital, routinely adding a cardiovascular ultrasonography of only 4.4 min with a pocket-size device corrected the primary diagnosis in 16% of patients. In addition, 29% had the primary diagnosis verified and in 10% an additional important diagnosis was made. Higher age predicted any diagnostic influence of pUS screening with an increase of 61% (P=0.003) per 10 years of higher age. Overall, the pUS screening had a sensitivity and specificity with respect to detecting at least moderate pathology of 97 and 93%. Positive and negative predictive values were 93 and 87%, respectively. In the sub-group of subjects with a change in the primary diagnosis following pUS there was no false-negative or false-positive findings. Screening by pUS assessed vascular and cardiac anatomy and function accurately and enabled correction of the diagnosis in 16% of patients admitted to a cardiac unit. In 55% of the participants, the cardiovascular ultrasound screening had important diagnostic influence. We suggest that it would be appropriate to implement strategies and systems for routinely adding an ultrasound cardiovascular examination to patients in cardiac units.